2017
DOI: 10.1016/j.redox.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic action of nitrite in sickle cell disease

Abstract: Sickle cell disease is caused by a mutant form of hemoglobin that polymerizes under hypoxic conditions, increasing rigidity, fragility, calcium influx-mediated dehydration, and adhesivity of red blood cells. Increased red cell fragility results in hemolysis, which reduces nitric oxide (NO) bioavailability, and induces platelet activation and inflammation leading to adhesion of circulating blood cells. Nitric Oxide inhibits adhesion and platelet activation. Nitrite has emerged as an attractive therapeutic agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 90 publications
3
30
0
Order By: Relevance
“…Hemoglobin acts as a sink that is able to store nitric oxide equivalents, whether it is nitrite or S‐nitrosylated proteins, for use in remote areas of the vasculature and can convert nitrite to NO under low oxygen conditions . Regional nitric oxide release inhibits platelet activation and aggregation, and could impact resting and hyperemic blood flow . Some data implicate mechanical stress and RBC deformation as stimuli for local NO .…”
Section: Discussionmentioning
confidence: 99%
“…Hemoglobin acts as a sink that is able to store nitric oxide equivalents, whether it is nitrite or S‐nitrosylated proteins, for use in remote areas of the vasculature and can convert nitrite to NO under low oxygen conditions . Regional nitric oxide release inhibits platelet activation and aggregation, and could impact resting and hyperemic blood flow . Some data implicate mechanical stress and RBC deformation as stimuli for local NO .…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide inhibits leukocyte adhesion and platelet adhesion and activation, thus blunting hemolysis and thromboinflammation associated with SCD. 10,101 Several agents that target different aspects of oxidant and nitric oxide biology have been used to modify SCD and reduce VOC events ( Table 1). Some of the particular interest are as follows.…”
Section: Antiplatelet and Anticoagulantsmentioning
confidence: 99%
“…However, in adults with SCD and mild to moderate ACS, nitric oxide therapy failed to show any reduction in treatment, suggesting that nitric oxide therapy is complex and requires further understanding. 64 The failure of inhaled nitric oxide may be because it mainly targets the lungs and was used under acute care settings, which may have been insufficient for I/RI affected tissues 101 with less systemic action.…”
Section: Nitrite Therapymentioning
confidence: 99%
“…123 In vitro studies and in vivo studies with transgenic SCD mice have shown that nitrite may also improve RBC deformability as well as reduce RBC, leukocyte, and platelet adhesion, in addition to reducing hemolysis. 93 When administered to a small number of individuals with SCD and in steady state, sodium nitrite infusions augmented plasma nitrite concentrations and augmented forearm blood flow without causing hypotension or clinically significant methemoglobinemia. 94 Potential for sGC agonist therapy in SCD While decreased NO signaling may play a major role in SCD pathophysiology, restoration of NO-dependent signaling more directly with NO inhalation and L-arginine supplementation in patients has shown limited efficacy, perhaps due to the fact that the mechanisms that limit NO production and bioavailability are sustained even during the therapy.…”
Section: No-based Therapies In Scdmentioning
confidence: 99%